Spatial Aspects of Restrictions on Registered Sex Offenders. Issue 2 (22nd January 2016) - Leipnik, Mark; Ye, Xinyue; Serna, Jose; Strong, James; Wilkins, Christopher; Wu, Ling
Abstract: Restrictions in the USA on registered sex offenders (RSOs) are examined from the spatial aspects. The long history of various restrictions imposed by government, particularly local ones, is covered in the introduction. Spatial aspects, such as delineation of zones from which certain activities or certain people are excluded is the focus. Then the nature of restrictions on RSOs is considered at the state, county and municipal level. Typical of restrictions are that RSOs are prohibited from moving into residence within a prescribed distance of certain features in a community. The distances are typically 1, 000 feet but are quite variable. Typical proscribed venues are schools, parks and day care centers, but there can be many others such as bus stops. Spatial aspects of these restrictions, such as how offender locations are geocoded and represented and how proscribed venues are delineated is analyzed. Specific details and theoretical concerns related to the many problematic issues with RSO restrictions is presented. In particular questions of their constitutionality and efficacy are raised. The paper concludes with a discussion of the implications of RSO restrictions for the discipline of geography in general and for the evolution of increasingly precise methods of spatial analysis in particular.